2011
DOI: 10.1007/s00284-011-9970-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Virulence of Xanthomonas campestris pv. campestris Mutant Strains Lacking Functional Genes in the OxyR Regulon

Abstract: Xanthomonas campestris pv. campestris causes black rot in cruciferous crops. Hydrogen peroxide (H(2)O(2)) production and accumulation is an important initial response in plant defense against invading microbes. The role of genes involved in the bacterial H(2)O(2) protection system in pathogenicity was evaluated. Mutants of katA (encoding a monofunctional catalase) and, to a lesser extent, katG (encoding a catalase-peroxidase) and oxyR (encoding a H(2)O(2) sensor and a transcription regulator), are hypersensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The exponential-phase cultures were challenged with 75 mM CuCl 2 for 15 min. Total RNA preparation and qRT-PCR were performed as previously described (Buranajitpakorn et al, 2011). Real-time PCR was executed using 20 ng cDNA, SYBR green PCR Master Mix (Applied Biosystems) and a specific primer pair for each gene.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The exponential-phase cultures were challenged with 75 mM CuCl 2 for 15 min. Total RNA preparation and qRT-PCR were performed as previously described (Buranajitpakorn et al, 2011). Real-time PCR was executed using 20 ng cDNA, SYBR green PCR Master Mix (Applied Biosystems) and a specific primer pair for each gene.…”
Section: Methodsmentioning
confidence: 99%
“…X. campestris pv. campestris ATCC 33913 (Xcc) wild-type and mutant strains were grown aerobically at 28 uC in Silva-Buddenhagen (SB) medium (Charoenlap et al, 2011) and plant-like medium XVM2 (Wengelnik & Bonas, 1996) as indicated. Exponential-phase cells (OD 600 of 0.5) were used in all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…campestris in a susceptible host plant was evaluated. The soxR mutant, the isogenic wild-type strain, and the soxR mutant harboring plasmid pSoxR (soxR/pSoxR) were inoculated into Chinese radish (Raphanus sativus) leaves using a leaf-clipping method described previously (4). The length of the black rot lesion was measured at 14 days postinoculation.…”
Section: Figmentioning
confidence: 99%